Effectiveness of non-biodegradable poly(2-hydroxyethyl methacrylate)-based hydrogel particles as a fibroblast growth factor-2 releasing carrier. Issue 11 (November 2015) - Takeda, Kahoru; Kitagawa, Haruaki; Tsuboi, Ririko; Kiba, Wakako; Sasaki, Jun-Ichi; Hayashi, Mikako; Imazato, Satoshi
Highlights We developed non-biodegradable hydrogel particle as drug carrier for dental resins. The release of BSA or FGF-2 from hydrogel particles could sustain for up to 14 days. The activity of FGF-2 was maintained for over 2 weeks within the particles. The hydrogel is promising for dental resins to provide tissue regenerative function.